2021
DOI: 10.1002/aqc.3514
|View full text |Cite
|
Sign up to set email alerts
|

Improving the detection of rare native fish species in environmental DNA metabarcoding surveys

Abstract: The presence of threatened or endangered species often strongly influences management and conservation decisions. Within the Murray–Darling Basin (MDB), Australia, the presence of threatened native fish affects the management and allocation of water resources. In New South Wales, these decisions are currently based on traditional fisheries data and a predictive MaxEnt model. However, it is important to verify the model's predictive power given the implication it may have, but this requires methods with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Testing primers in vitro would further elucidate the mechanisms underlying false negatives. In practice, more taxon‐specific primers (e.g., Bálint et al, 2018; Valentini et al, 2016), blocking primers (Rojahn et al, 2021), or additional primer sets targeting different genetic markers (Collins et al, 2019) could be used to enhance the detection of focal taxa relative to other vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Testing primers in vitro would further elucidate the mechanisms underlying false negatives. In practice, more taxon‐specific primers (e.g., Bálint et al, 2018; Valentini et al, 2016), blocking primers (Rojahn et al, 2021), or additional primer sets targeting different genetic markers (Collins et al, 2019) could be used to enhance the detection of focal taxa relative to other vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…They found that curves began to flatten only after this relatively higher level of replication and predicted that species accumulation would plateau with 10–20 replicates. More recently, Rojahn et al ( 2021 ), while exploring the effect of PCR replication for detecting rare species of fish, suggested that high PCR replication is not sufficient in some cases to detect rare taxa, in particular where common taxa may swamp the PCR and inhibit detection.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, bowhead whale (Balaena mysticetus) eDNA was found to diminish substantially in water samples collected as little as 10 min after the whale presence (Székely et al, 2021). The reported challenges in detecting cetacean eDNA suggest that the results from our pilot study using novel primers optimized to for cetaceans are encouraging (Valsecchi et al, 2020), given that a) they allow for amplification of all vertebrate taxa, meaning low-prevalence eDNA could be overwhelmed by high abundance targets (Rojahn et al, 2021); and b) metabarcoding is less sensitive to detecting rare signals than species specific qPCR assays (Harper et al, 2018;Qu and Stewart, 2019).…”
Section: Cetofauna Detectionmentioning
confidence: 76%